Agronomic responses and sugarcane aphid pressure in warm‐season annual forage mixtures. Issue 2 (23rd June 2021) - Thompson, Serena Joy; Jacobson, Alana; Severino da Silva, Liliane; Dillard, Sandra Leanne
Abstract: Warm‐season annual forages are a viable option to complement perennial forage systems. Sugarcane aphid [SCA; Melanaphis sacchari ] has emerged as a significant pest in Sorghum spp. compromising forage production. This study evaluated herbage responses and SCA incidence in monoculture and mixtures of cowpea ( Vigna unguiculata L. Walp), crabgrass ( Digitaria sanguinalis L.), and sorghum × sudangrass [( Sorghum bicolor L. Moench) × ( Sorghum × drummondii )]. Crude protein (CP), lignin, acid detergent fiber (ADF) and neutral detergent fiber (NDF) concentrations were determined. Incidence of SCA was evaluated weekly on sorghum × sudangrass treatments. Herbage mass was not affected ( P  = .522) by treatments and ranged from 1, 361 to 2, 104 lb dry matter (DM) acre –1 . Greater herbage mass was observed in Year 1 than 2 (1, 678 vs. 1, 050 lb DM acre –1 ) most likely associated with higher rainfall on Year 1. Greater ( P  < .001) CP was observed in Year 2 and was also associated with mixtures containing cowpea. For treatments containing sorghum × sudangrass, the use of insecticide decreased losses in forage production, although sorghum × sudangrass mixtures did not result in a reduction of SCA when compared to its monoculture. This response is most likely associated with less sorghum × sudangrass plant density in mixtures which may have resulted in a higher SCA incidence per plant. Based on our results, the use of warm‐season annuals is a viable option to complement forage production; however, the use of insecticide may be needed to reduce yield and economical losses due to SCA. Core Ideas: Forage mass was not affected by species composition. Mixtures containing cowpea had greater nutritive value. The use of forage mixtures did not reduce aphid density. The use of insecticide is recommended to decrease losses in sorghum × sudangrass yield.